Newspaper Coverage Effects on the Promotion of a Lifestyle Intervention Program - Sindre M. Dyrstad; Leif I. Tjelta (Journal of Obesity)
The study’s purpose was to measure the impact of an individually designed lifestyle intervention program on the readers of a regional newspaper. A newspaper with 180,000 daily readers covered a story about three untrained and overweight adults who participated in an individually designed lifestyle intervention program. Their goals were to become physically fit and run a half marathon (21.1 km) after 14 weeks of training. The newspaper published on average three weekly articles throughout the project period, including the weekly training program and a record of the physical improvements made by the participants. The number of hits on the project’s web site was recorded. Spin-off effects on the responses of readers were mapped. The project's web site had 25,000 unique weekly hits. Significant spin-off effects included the establishment of training groups which were still active after two years and the launch of a similar project by another regional newspaper. This individually designed lifestyle intervention program was successfully scaled up and reached a large number of the newspaper’s readers. The collaboration between a newspaper and exercise researchers could also be adapted to other press media and represents a novel approach to improve participation in physical activities.